Evaluation of the Integrative Holistic-Based Al-Islam Kemuhammadiyahan and Arabic Language (ISMUBA) Curriculum at SMA Muhammadiyah Sidoarjo: Evaluasi Kurikulum Al-Islam Kemuhammadiyahan Dan Bahasa Arab (ISMUBA) Berbasis Holistik Integratif Di SMA Muhammadiyah Sidoarjo - Hikmah, Khizanatul; Amrullah, Muhlasin; Chotimah, Chusnul; Alfarisi, Mafajah Salsabila (Halaqa: Islamic Education Journal, 2020)
Muhammadiyah High Schools in Sidoarjo Regency has become as a pilot project education researchers in the scheme organized by PP Muhammadiyah’s Diktilitbang Assembly. This research aims to study and analyze the planning, implementation, and evaluation of the Holistic-Integrative-based ISMUBA curriculum in Muhammadiyah High Schools in Sidoarjo Regency with the context, input, process and product (CIPP) evaluation model. The data collection techniques used by researchers are observation, interview and documentation techniques. Then the researchers analyzed the data using the Miles & Hiberman design, namely data reduction, presentation, conclusion and verification. ISMUBA curriculum implementation process in accordance with the guidance of the Dikdasmen assembly based on a comprehensive and integrated holistic curriculum base through curriculum content standarts, centered on the potential, development, needs of students, combining knowledge and Islam, and forming and instilling habits of Islamic values in school, and a small note related to Arabic learning of Muhammadiyah 3 Tulangan high school and Muhammadiyah 4 Porong high school are still classified as using the classical system.